Conditional Death Penalty Policy in Law Number 1 of 2023 concerning the Criminal Code is Linked to the Principle of Legal Certainty - Amiratul Mardhiyah Putri; Evi Deliana HZ; Syaifullah Yophi Ardiyanto (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2024)
Conditional death penalty aims to provide an opportunity for convicts to rehabilitate themselves and change for the better. Conditional death penalty also aims to reduce the risk of execution of innocent people, show a humanist attitude and respect for human rights, and accommodate various conflicting views and interests regarding the death penalty in Indonesia. Conditional death penalty is regulated in Article 100 Paragraph of Law Number 1 of 2023 concerning the Criminal Code. The type of research to be carried out is normative legal research. From the perspective of its objectives, normative legal research can be divided into 7 (seven) types, namely in this case research is carried out on the principles of law, namely regarding the Implementation of Conditional Death Penalty in Law Number 1 of 2023 concerning the Criminal Code in the Perspective of Legal Certainty.